Perceptions and Reported Use of Information Technology (IT) Anglicisms by Spanish University Students - Núñez Nogueroles, Eugenia Esperanza; Luján-García, Carmen (Miscelánea: A Journal of English and American Studies, 2022)
This paper presents a twofold analysis that, on the one hand, is intended to examine the presence of IT Anglicisms in the contemporary Spanish digital press; on the other hand, it aims to reveal the degree of knowledge and use of these English lexical items by a sample of Spanish speaking university students and to explore what their perceptions and attitudes are towards Anglicisms and their use ‒not only in specialised contexts such as the IT field, but also when dealing with current and more general topics. The administration of a questionnaire to 232 pupils studying various degrees in two Spanish universities provided reliable data of the high level of knowledge and reported use of a sample of IT terms extracted from an Anglicisms search tool, ‘Observatorio Lázaro’. In addition, the findings have shown open and positive perceptions by Spanish students towards the usage of Anglicisms. Various pragmatic functions (expressive and referential) seem to motivate these uses. Finally, some pedagogical implications of this study are discussed in the sphere of ESP teaching/learning.
Keywords: Anglicisms; Information Technology (IT); borrowings; perceptions by Spanish students; pragmatic functions; pedagogical implications